Formulation and Antibacterial Studies of Ethanolic Leaf Extract of Ziziphus mauritania Herbal Cream - Okpanachi, G.O.; Oduola, A.R.; Adamu, O.J; Auwal, M.A.; Jidda R. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Ziziphus mauritania leaves, fruits and seeds are used by Nigerian traditional herbalists for treatment of various ailments. This study investigated antibacterial property of ethanolic leaf extract which was formulated into Ziziphus mauritania herbal cream. The antibacterial activity of the ethanolic leaf extract was conducted against Staphylococcus aureus using cup plate method and was compared with Linezolid, Augmentin, Vancomycin and Cefpodoxime. The minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) were determined. The extract-excipients compatibility tests were carried out using FTIR. The herbal cream was formulated at 1-5 % w/w after preparing the aqueous and oily phase and thereafter the cream was evaluated after 48 h. The extract had comparable antibacterial activity with Augmentin, Linezolide, Cefpodoxime and Vancomycin at concentrations of 1.56, 3.13, 6.25, 12.5, 25.0 and 50.0 mg/mL. The FTIR spectra of the extract-excipients mixtures revealed no additional peaks thereby implying that no possible interaction occurred. The formulated herbal cream passed the evaluation tests such as pH, appearance, viscosity, irritancy, type of smear. Herbal cream of Ziziphus mauritania leaves extract was formulated. The antibacterial action of the extract justified its traditional use in wound healing and because the herbal cream had no adverse effects on the skin, the formulation can be used externally in the treatment of various infections caused by Staphylococcus aureus.